2017
DOI: 10.1093/cid/cix854
|View full text |Cite
|
Sign up to set email alerts
|

Time to Switch to Second-line Antiretroviral Therapy in Children With Human Immunodeficiency Virus in Europe and Thailand

Abstract: One in 5 children switched to a second-line regimen by 5 years of ART, with two-thirds failure related. Advanced HIV, older age, and NVP-based regimens were associated with increased risk of switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Data from the EPPICC Paediatric merger 2014 ( n = 3953) were used, as described previously [23,24]. In brief, the EPPICC merged individual patient data on routine demographic, clinical, laboratory and treatment-related variables from 19 observational cohorts across 17 countries prepared according to a standardised data specification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the EPPICC Paediatric merger 2014 ( n = 3953) were used, as described previously [23,24]. In brief, the EPPICC merged individual patient data on routine demographic, clinical, laboratory and treatment-related variables from 19 observational cohorts across 17 countries prepared according to a standardised data specification.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated the following factors: age at cART initiation, baseline viral load, CD4 + % and cell count, sex, ethnicity, initial cART regimen (bPI or NNRTI and two or more NRTI), infant antiretroviral prevention of mother-to-child transmission (PMTCT) prophylaxis regimen given within 4 weeks of birth, maternal antiretroviral PMTCT regimen used in the prenatal and delivery period, birth abroad (whether infants were born in the same country in which they were enrolled for HIV care), year of birth, year of cART initiation, Centers for Disease Control and Prevention (CDC) C event by cART initiation and geographical region. Geographical region of cohort was categorised a priori , as described previously [24]: Eastern Europe (Russia and Ukraine), Central and Western Europe (Belgium, Germany, Italy, Netherlands, Poland, Portugal, Romania, Spain, Sweden, Switzerland, France and Greece), United Kingdom/Ireland and Thailand. Missing values for baseline viral load (18%) and CD4 + % (22%) were multiply imputed by chained equations (20 cycles), on the complete EPPICC dataset to avoid imputation bias.…”
Section: Methodsmentioning
confidence: 99%
“…Ninety percent of switches to second‐line ART in our study had confirmed VF, with a median time to switch of 1.5 years. Our finding indicates a lower cumulative incidence of switching to second‐line ART after 3 years of rapid ART initiation (5.3%) compared to an individual patient data meta‐analysis study from Thailand (8%) and Europe (14–16%) before the era of treating at any CD4 levels [ 39 ]. Moreover, the proportion with confirmed VF with switching to second‐line ART in our study was also higher than adults living with HIV where rates ranged from 43% to 66% in studies from Eswatini, Uganda and Lesotho [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 86%
“…Second-and third-line antiretroviral treatments (ART) are needed for children and adolescents living with HIV who experience treatment failure and have limited ART options, due to multidrug resistance or drug intolerance [1][2][3]. Etravirine is a second-generation non-nucleoside reversetranscriptase inhibitor (NNRTI) approved for use as part of second or third-line ART in children and adolescents aged ≥6 years [4].…”
Section: Introductionmentioning
confidence: 99%